Contribution to the knowledge of Rhaphidophorinae (Orthoptera: Ensifera: Rhaphidophoridae) from Thailand: three genera Neorhaphidophora, Eurhaphidophora and Minirhaphidophora - Dawwrueng, Pattarawich; Gorochov, Andrei V.; Tanomtong, Alongklod; Suwannapoom, Chatmongkon (Zootaxa, 2020)
A new subgenus, three new species and a new subspecies of the rhaphidophorines are described from Thailand: Minirhaphidophora (Condylophora) ophioglossa subgen. et sp. nov., Neorhaphidophora siamensis sp. nov., Eurhaphidophora pawangkhananti sp. nov., and Eurhaphidophora tarasovi doitungensis ssp. nov. Keys to all known species with regard to the genera Neorhaphidophora and Minirhaphidophora, as well as a key to the Thai species of the genus Eurhaphidophora, are provided.